2023
DOI: 10.1128/spectrum.05297-22
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation, Risk Factors, Spatial-Temporal Cluster, and Epidemic Trend Analysis of Pseudorabies Virus Seroprevalence in China (2017 to 2021)

Abstract: PRV is a critical pathogen threatening the global swine industry. Our research fills knowledge gaps regarding PRV prevalence, infection risk factors, spatial-temporal clustering of high PRV gE seroprevalence, and the epidemic trend of PRV gE seroprevalence in China in recent years. These findings are valuable for the clinical prevention and control of PRV infection and suggest that PRV infection is likely to be successfully controlled in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Berke et al ( 39 ) detected the spatial aggregation of two PRV infections in Germany, with radii of 2.6 and 1.7 km, and relative risk values of 2.4 and 3.3, respectively. Zhao et al ( 22 ) detected five significant high PRV gE seroprevalence groups in China for the first time in their data from 2017 to 2021. However, research on PRV spatiotemporal clustering in China is still relatively limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berke et al ( 39 ) detected the spatial aggregation of two PRV infections in Germany, with radii of 2.6 and 1.7 km, and relative risk values of 2.4 and 3.3, respectively. Zhao et al ( 22 ) detected five significant high PRV gE seroprevalence groups in China for the first time in their data from 2017 to 2021. However, research on PRV spatiotemporal clustering in China is still relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…It has led to significant changes in herd distribution, farm biosecurity levels, and herd circulation strategies within the swine farming industry. Zhao et al found that pig farms sampled after the ASF outbreak demonstrated a lower likelihood of PRV infection compared to those sampled before the outbreak ( 22 ). This could be attributed to enhanced biosafety management practices.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the viral genome has revealed that the newly emerged PRV variant belongs to a strain variant of genotype 2. In recent years, extensive serological molecular epidemiological studies on PRV infection have been conducted in pig populations in China to better control the spread of the novel variant strains (Zhao et al, 2023). The prevalence of PRV infection is influenced by various factors such as region, sample size, and season.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudorabies (PR) is a disease caused by the pseudorabies virus (PRV), which belongs to the herpesvirus family [14][15][16]. Despite the fact that PR has been eradicated in several countries, variant strains of PRV remain prevalent in China [17]. PR is a notable disease, causing substantial economic losses for the swine industry, with pigs being vulnerable to PR.…”
Section: Introductionmentioning
confidence: 99%